Molecular Dynamic Simulation Study on Thermal Decomposition Mechanism of Cellulose - Huang, Jinbao; Tong, Hong; Zeng, Guisheng; Xie, Yu; Li, Weimin (Asian Journal of Chemistry, 2013)
Cellulose is the most elementary component in biomass, of which thermal decomposition behaviour embodies the whole thermal decomposition law of biomass to a large extent. In order to ascertain the cellulose thermal decomposition mechanism and the formation mechanism of main products from the microscopic perspective, the thermal decomposition processes of cellulose single molecule with 10 monomers were investigated by molecular dynamic simulation method. The simulation results show that hydroxyl bonds begin to break when temperature reaches 450 K. While as the temperature increases to ca. 600 K, cellulose monomers get to be formed by glucoside bonds rupture; and pyranoid rings becomes open and all kinds of molecular fragments are formed at the same time. Based on the previous experimental results, the possible formation pathways of major products through reactions of all kinds of molecular fragments were analyzed.